2019
DOI: 10.1109/access.2019.2927691
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Flow Resistance Over Rigid Vegetated Channel

Abstract: Vegetation is an important part of the ecological channel, and flow structure over vegetation in ecological channel is rather complex. The vegetation resistance to flow is affected by many factors, and there is still no general calculation method to express it. Thus, it is necessary to explore the mechanism of flow resistance over vegetation in open channel. In this paper, the rigid cylindrical sticks arranged in the open channel were used to simulate the stems of non-submerged vegetation in order to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The load cell is located at the middle part of the experimental section. The working principle of load cell has been detailed in the Liu et al [32]. As shown in Fig.5, only the vegetation sticks interacts with flow and the experimental board (it can be viewed as ''channel bed'') is not 'submerged in flow so the skin friction does not act on the load cell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The load cell is located at the middle part of the experimental section. The working principle of load cell has been detailed in the Liu et al [32]. As shown in Fig.5, only the vegetation sticks interacts with flow and the experimental board (it can be viewed as ''channel bed'') is not 'submerged in flow so the skin friction does not act on the load cell.…”
Section: Methodsmentioning
confidence: 99%
“…The x is the flow direction and y is the flow depth direction of channel. The working principle has been explained in detail by Liu et al's study [32]. The Fig.7 shows longitudinal average flow velocity and the experimental condition is the Q = 100m 3 /h and one-row sticks act as one vegetation patch.…”
Section: A Determination Of the Longitudinal Scale Of The Vortex Strmentioning
confidence: 99%
“…In 1959, Chow suggested in the look-up tables of his book that the vegetation component of Manning's coefficient could be 0.1 with very high vegetation [3]. This traditional method is not very accurate because of the complexity of vegetation types, densities and distributions [33], [34]. The theoretical considerations and experimental analysis on the variation of the water depth of gradually varied flow in the vegetated channel in this study revealed that the Manning's coefficient varied along the flow direction and that such variation had a certain regularity.…”
Section: B Variations Of the Total Manning's Coefficient Along The Vegetated Channelmentioning
confidence: 99%
“…Behind the advantages of sided vegetation from increases bank stability, reduces erosion, provides habitat for aquatic life, and filters pollutants [1,2], its excessive existence of it causes many hydraulic problems. Such as water velocity reduction, water level rising, decrease water flow, un-efficient water distribution, etc.…”
Section: Introductionmentioning
confidence: 99%